2017
DOI: 10.3889/oamjms.2017.083
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary Sinus Augmentation Using a Titanium Mesh: A Randomized Clinical Trial

Abstract: BACKGROUND:Various attempts have been implemented using different materials and techniques to augment the maxillary sinus floor for prospect dental implant positioning.AIM:This contemplate was conducted to assess the osteogenic capability of the maxillary sinus in a two-step sinus membrane elevation using titanium mesh to keep the formed space to place dental implants in atrophic ridges.MATERIALS AND METHODS:Titanium micromesh was customized and positioned into the sinus on one side to preserve the elevated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Grafting the sites is thought to improve the primary stability by providing more bone onto which the implant can anchor [13, 37]. Moreover, the application of grafting material is thought to create and maintain the space for new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Grafting the sites is thought to improve the primary stability by providing more bone onto which the implant can anchor [13, 37]. Moreover, the application of grafting material is thought to create and maintain the space for new bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of this mixture was advocated by the authors who reported better new bone formation and faster healing 29,30 , however this subject is still controversial as a recent meta-analysis showed no evidence on the necessity of adding PRF to the grafting material. 31 In a case series, Atef et al 32 used a titanium mesh as space maintainer in a lateral graftless sinus lift and found promising results so Bahaa-eldin et al 33 performed a pilot study where they were able to place an implant in the newly formed bone under the titanium mesh but they reported that the density of this bone was far less than that of the bovine xenograft.…”
Section: Cone-beam Computed Tomography (Cbct)mentioning
confidence: 99%